2013
DOI: 10.3727/096368912x657440
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Three-Dimensional PDMS Scaffolds for Extrahepatic Islet Transplantation

Abstract: Clinical islet transplantation has demonstrated success in treating type 1 diabetes. A current limitation is the intrahepatic portal vein transplant site, which is prone to mechanical stress and inflammation. Transplantation of pancreatic islets into alternative sites is preferable, but challenging, as it may require a three-dimensional vehicle to confer mechanical protection and to confine islets to a well-defined, retrievable space where islet neovascularization can occur. We have fabricated biostable, macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
122
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 74 publications
1
122
0
Order By: Relevance
“…Recent approaches, however, have sought to generate an integrated islet graft site through the use of macroporous scaffolds. [13][14][15] This approach seeks to create intimacy between the islets and the surrounding environment, while also providing a platform for modulation and control of the local transplant site. Our laboratory has demonstrated, in rat and nonhuman primate models, that the use of a poly(dimethylsiloxane) (PDMS) macroporous scaffold within an alternative transplant site can be highly effective in restoring normoglycemia.…”
mentioning
confidence: 99%
“…Recent approaches, however, have sought to generate an integrated islet graft site through the use of macroporous scaffolds. [13][14][15] This approach seeks to create intimacy between the islets and the surrounding environment, while also providing a platform for modulation and control of the local transplant site. Our laboratory has demonstrated, in rat and nonhuman primate models, that the use of a poly(dimethylsiloxane) (PDMS) macroporous scaffold within an alternative transplant site can be highly effective in restoring normoglycemia.…”
mentioning
confidence: 99%
“…In addition, the frequent changes in blood glucose levels and high glucose concentrations are known to be deleterious to the islets. Therefore, many studies have pursued alternative sites with a more adequate microenvironment for pancreatic islet transplantation, such as organs (renal subcapsule, omentum, peritoneum, subcutaneous site, muscle) (14-16), various vascular sites (celiac artery, vein, spleen, lung) (17,18), immunoprivileged sites (testis, thymus) (19,20), or devices and capsules (21)(22)(23)(24)(25). These may optimize engraftment, survival, and function as well as decrease immunogenicity and promote proliferation and regeneration.…”
mentioning
confidence: 99%
“…In 2014, Pagliuca et al, and Rezania et al both reported successful validation of a seven-stage protocol to generate insulin-secreting cells that were able to reverse hyperglycemia in diabetic mice within months after transplantation [163,164]. These recent developments represent significant breakthroughs in developing a cure for T1D using hESC transplantation.…”
Section: Human Embryonic Stem Cells (Hescs)mentioning
confidence: 99%
“…Pancreatic stem cells [160,161], hESCs [162][163][164], induced pluripotent stem cells (iPSCs) [165][166][167][168][169], mesenchymal [170][171][172][173][174] and adipose-derived stem cells (ADSCs) [175,176] have all been used to derive islet-like cell clusters or insulin-producing cells (IPCs) that are viable, express markers similar to terminally differentiated β-cells (Insulin, GLUT2) and are able to respond to a glucose challenge. These cells have all demonstrated good function after encapsulation within bioencapsulation devices and several in vivo studies have also been conducted.…”
Section: Recent Developments In Stem Cell Therapy For T1dmentioning
confidence: 99%